Binuclear Sulfide Niobium Clusters Coordinated by Diimine Ligands: Synthesis, Structure, Photocatalytic Activity and Optical Limiting Properties. Issue 17 (19th May 2015) - Rogachev, Alexander V.; Gushchin, Artem L.; Abramov, Pavel A.; Kozlova, Ekaterina A.; Vicent, Cristian; Piryazev, Dmitry; Barlow, Adam; Samoc, Marek; Humphrey, Mark G.; Llusar, Rosa; Fedin, Vladimir P.; Sokolov, Maxim N.
Abstract: Substitution reactions of binuclear niobium cluster anion [Nb2 S4 (NCS)8 ] 4– with different types of pyridine‐based diimine ligands have been carried out. In the case of 2, 2′‐bipyridine (bipy) and its derivatives, only monosubstituted complexes [Nb2 S4 (NCS)6 L] 2– have been isolated. In the case of 1, 10‐phenanthroline and 2‐(2‐pyridyl)benzimidazole (Hpbz), both mono‐ and disubstituted complexes, [Nb2 S4 (NCS)6 L] 2– and [Nb2 S4 (NCS)4 L2 ], respectively, have been obtained. Crystal structures of (Et4 N)2 [Nb2 S4 (NCS)6 (bipy)]· 0.5bipy· 0.7CH3 CN and [Nb2 S4 (pbmz)2 (NCS)4 ]· 5DMF· 0.8H2 O have been determined. All compounds have been characterized by NMR, ESI mass spectrometry, IR, UV/Vis spectroscopy, and CV. TiO2 nanoparticles modified with (Et4 N)2 [Nb2 S4 (NCS)6 (bipy)] show moderate photocatalytic activity in the reaction of H2 generation from water in the presence of Na2 S/Na2 SO3 as a sacrificial electron donor system. The linear and nonlinear optical properties of the complexes with bipyridine ligands have been studied; the complexes function as broad‐band optical limiters. Abstract : A series of complexes, [Nb2 S4 (NCS)6 L] 2– and [Nb2 S4 (NCS)4 L2 ], where L is a bipyridine, phenanthroline or 2‐(2‐pyridyl)benzimidazole has been prepared. TiO2 nanoparticles modified with (Et4 N)2 [Nb2 S4 (NCS)6 (bipy)] exhibit photocatalytic activity for H2 generation from water in the presence of a sacrificial electron‐donor system. The complexes function as optical limiters.